THE EXPRESSION OF COLLECTIVE ASSOCIATION IN THE SPEECH OF CHILDREN UP TO SCHOOL AGE (ON THE EXAMPLE OF LEXICAL ASSOCIATIONS IN ANTI-SEMITIC AND ENANTIOSEMIC CONTEXTS) - Mirnosirova Dilbar Nodirbek kizi (Journal Park Publishing, 2023)
The article provides an analysis of collective associations of antisemitic and enantiosemic attitudes observed in the speech of preschool children, which uses such types of linguistic research methods as description, classification, and component analysis.
Keywords: association, individual lexical association, collective lexical association, antisemy, antonymy, enantiosemy, stimulus, response reaction.